Meaning of conservatism - "Scruton, Roger" (London, 1984)
First published in 1980, The Meaning of Conservatism is now recognized as a major contribution to political thought, and the liveliest and most provocative modern statement of the traditional conservative position. Roger Scruton challenges those who would regard themselves as conservatives, and also their opponents. Conservatism, he argues, has little in common with liberalism, and is only tenuously related to the market economy, to monetarism, to free enterprise or to capitalism. It involves neither hostility towards the state, nor the desire to limit the state's obligation towards the citizen. Its conceptions of society, law and citizenship regard the individual not as the premise but as the conclusion of politics. At the same time it is fundamentally opposed to the ethic of social justice, to equality of station, opportunity, income and achievement, and to the attempt to bring major institutions of society - such as schools and universities - under government control.
Keywords: Conservation